Thermoplastic wear-resistant composite material as well as preparation method and application thereof

By adding modified aramid fibers and modified molybdenum disulfide to the wear-resistant materials, the problems of high brittleness, insufficient toughness and poor filler dispersion are solved, and the low friction and high toughness characteristics of thermoplastic wear-resistant composite materials are achieved, extending service life and improving application performance.

CN119775692AActive Publication Date: 2025-04-08上海恒能轴承有限公司

Patent Information

Application Number
CN202411985617.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing wear-resistant materials such as polytetrafluoroethylene and polyphenylene sulfide have problems such as high brittleness and insufficient toughness, resulting in a shortened service life, and the added filler molybdenum disulfide is prone to agglomeration and poor dispersion, which affects the lubricating performance.

Method used

Using polytetrafluoroethylene and polyphenylene sulfide as the main components, modified aramid fibers and modified molybdenum disulfide are added. By improving the surface activity and UV resistance of the modified aramid fibers, and improving the dispersion of the modified molybdenum disulfide, a thermoplastic wear-resistant composite material with low friction and high toughness is formed.

Benefits of technology

It realizes the low friction and high toughness characteristics of thermoplastic wear-resistant composite materials, extends the service life of the material, and improves its application performance in components such as pump bodies and bearings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of wear-resistant materials, and provides a thermoplastic wear-resistant composite material as well as a preparation method and application thereof, and the thermoplastic wear-resistant composite material comprises the following raw materials in parts by weight: 65-75 parts of polytetrafluoroethylene, 25-35 parts of polyphenylene sulfide, 3-7 parts of modified aramid fiber and 1-5 parts of modified molybdenum disulfide. The thermoplastic wear-resistant composite material provided by the invention has the characteristics of good wear resistance, low friction and high toughness, and can be widely applied to wear-resistant parts related to pump bodies and bearings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wear-resistant materials, and in particular to a thermoplastic wear-resistant composite material and a preparation method and application thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE) is a high molecular polymer made by polymerizing tetrafluoroethylene as a monomer. It has excellent wear resistance, corrosion resistance, aging resistance, high and low temperature resistance and other characteristics. It can be used as the main component of wear-resistant materials and is widely used in parts such as bearings on pump bodies in chemical processes to ensure the smooth operation of pump shafts. Similarly, polyphenylene sulfide (PPS) is a new type of high-performance thermoplastic resin with good thermal stability, chemical corrosion resistance and wear resistance, and also has good application prospects in the field of wear-resistant materials.

[0003] Although polytetrafluoroethylene and polyphenylene sulfide have many excellent characteristics as wear-resistant materials on pumps and have good application prospects, there are still some unresolved problems. For example, polytetrafluoroethylene and polyphenylene sulfide both have the problems of large brittleness and insufficient toughness, which may shorten the service life of wear-resistant materials; in addition, long-term friction leads to wear of parts, which is an important reason for the short service life of various equipment and the inability of equipment to work stably. In order to further extend the overall service life of wear-resistant materials, people often add some lubricating fillers such as molybdenum disulfide, but molybdenum disulfide has the problems of easy agglomeration and poor dispersion, which will cause its lubrication performance to not be well exerted.

[0004] Patent CN1699474A discloses a hybrid reinforced high-performance composite material for bearings, a manufacturing method and its application, which is composed of chopped carbon fibers, high-temperature resistant resins and fillers. The high-temperature resistant resin is polyphenylene sulfide, polyether ketone or polyimide, which has a good wear-resistant effect. The filler is graphite, polytetrafluoroethylene or molybdenum disulfide, which can play a lubricating role. However, both graphite and molybdenum disulfide have the problems of easy agglomeration and poor dispersion, which may cause the lubrication performance of the material to fail to achieve the ideal effect.

[0005] Therefore, there is an urgent need in the market for a thermoplastic wear-resistant composite material with low friction and high toughness. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention uses polytetrafluoroethylene and polyphenylene sulfide as main components, adds modified aramid fiber and modified molybdenum disulfide to synthesize a thermoplastic wear-resistant composite material, which has the characteristics of good wear resistance, low friction and high toughness.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On one hand, the present invention provides a thermoplastic wear-resistant composite material, which comprises the following raw materials by weight: 65-75 parts of polytetrafluoroethylene, 25-35 parts of polyphenylene sulfide, 3-7 parts of modified aramid fiber, and 1-5 parts of modified molybdenum disulfide.

[0009] In some embodiments of the present invention, the particle size of the polyphenylene sulfide is 550-650 mesh.

[0010] Preferably, the particle size of the polyphenylene sulfide is 600 mesh.

[0011] The applicant selects polyphenylene sulfide with this particle size because it has excellent mechanical properties, thermal stability and good processing performance.

[0012] In some embodiments of the present invention, the method for preparing the modified aramid fiber comprises the following steps:

[0013] (1) γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, anhydrous ethanol and deionized water are mixed, the pH is adjusted to 5-6, the mixture is heated to 55-65° C., stirred for 3.5-4.5 h, and dried to obtain product 1 for later use;

[0014] (2) Fuming nitric acid, concentrated sulfuric acid, acetic anhydride and glacial acetic acid are mixed and stirred to obtain solution 1 for use; potassium dihydrogen phosphate, dipotassium hydrogen phosphate and sodium borohydride are added to tetrahydrofuran and stirred to obtain solution 2 for use; aramid fiber is sequentially soaked in acetone, petroleum ether and deionized water, heated to reflux, filtered, vacuum dried and then added to solution 1, stirred at 5-15° C. for 5-7 h, filtered, washed, dried and then added to solution 2, stirred for 23-25 ​​h, filtered, washed and dried to obtain product 2 for use;

[0015] (3) adding sodium hydroxide aqueous solution to the product 1 of step (1), stirring, adding the product 2 of step (2), stirring at 55-65° C. for 3.5-4.5 h, filtering, washing, and drying to obtain product 3 for standby use;

[0016] (4) Add dopamine hydrochloride to deionized water, stir, add sodium hydroxide aqueous solution, add graphene oxide, stir at 20-40° C. for 14-16 h, add the product 3 of step (3), shake for 9-11 h, filter, wash, and dry to obtain modified aramid fiber.

[0017] Wherein, in the step (1), the mass ratio of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, anhydrous ethanol and deionized water is 1: (1-1.1): (2-2.5): (1-1.05);

[0018] In step (2), the ratio of aramid fiber to fuming nitric acid is 1 g: (1-1.5) ml.

[0019] In some embodiments of the present invention, in step (3), the mass ratio of product 2 to product 1 is 1:(3.5-4.5).

[0020] Preferably, in step (3), the mass ratio of product 2 to product 1 is 1:4.

[0021] In some embodiments of the present invention, in step (4), the mass ratio of product 3 to graphene oxide is 1:(0.01-0.03).

[0022] Preferably, in step (4), the mass ratio of product 3 to graphene oxide is 1:0.02.

[0023] Aramid fiber has good toughness and strength due to its unique molecular structure, which enables it to act as a toughening material in plastic systems. However, it has two inherent disadvantages, namely low surface activity and poor UV resistance, which seriously affect the application of aramid fiber.

[0024] On the one hand, the applicant firstly uses γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane as raw materials and controls the mass ratio of the two, hydrolyzes them in anhydrous ethanol and deionized water to prepare a polysiloxane with a hyperbranched structure (product 1), and then uses a solution composed of fuming nitric acid, concentrated sulfuric acid, acetic anhydride and glacial acetic acid, as well as potassium dihydrogen phosphate, dipotassium hydrogen phosphate, sodium borohydride and tetrahydrofuran to modify the aramid fiber, introduces amino groups into the surface of the aramid fiber (product 2), and further grafts the hyperbranched polysiloxane onto the surface of the aramid fiber, introduces a large number of active functional groups into the surface of the aramid fiber, improves the surface adhesion, and thus improves the aramid fiber. The problem of low fiber surface activity is solved, and the grafting of the hyperbranched structure also effectively resists the damage of ultraviolet rays to aramid fibers, thereby improving the ultraviolet resistance of aramid fibers to a certain extent; on the other hand, the applicant introduces graphene oxide to further graft and modify the above-mentioned modified aramid fibers. The rich oxygen-containing functional groups on the surface of graphene oxide give it good ultraviolet protection, and its unique chemical structure gives it good toughness, thereby greatly improving the ultraviolet resistance and toughness of the modified aramid fibers. In addition, the carboxyl groups on the surface of graphene oxide and the residual amino groups on the surface of aramid fibers may produce certain hydrogen bonds, thereby improving the stability and durability of the modified aramid fibers.

[0025] In some embodiments of the present invention, the method for preparing the modified molybdenum disulfide comprises the following steps:

[0026] 1) adding molybdenum disulfide and sodium tartrate to an aqueous solution of N-methylpyrrolidone, ultrasonicating, centrifuging, removing the supernatant, repeating the above operation, centrifuging, taking the precipitate, washing, drying, and obtaining an intermediate product for standby use;

[0027] 2) adding maleic anhydride into deionized water, stirring to obtain a solution for use, adding the intermediate product of step 1) into anhydrous ethanol, ultrasonicating, condensing and refluxing, adding the solution, stirring, filtering, washing, drying, and crushing to obtain modified molybdenum disulfide.

[0028] In some embodiments of the present invention, in step 1), the mass ratio of molybdenum disulfide to sodium tartrate is 1:(0.1-0.2).

[0029] Preferably, in step 1), the mass ratio of molybdenum disulfide to sodium tartrate is 1:0.16.

[0030] In some embodiments of the present invention, in step 2), the mass ratio of the intermediate product to maleic anhydride is 1:(0.3-0.5).

[0031] Preferably, in the step 2), the mass ratio of the intermediate product to maleic anhydride is 1:0.4.

[0032] Molybdenum disulfide has good lubrication effect. Adding it to wear-resistant composite materials can effectively reduce friction and increase the service life of wear-resistant composite materials. However, molybdenum disulfide has the problems of easy agglomeration and poor dispersion, which will lead to its lubrication performance not being fully exerted.

[0033] The applicant uses an aqueous solution of N-methylpyrrolidone as a dispersant and adds sodium tartrate as an intercalation compound to perform an exfoliation treatment on molybdenum disulfide to prepare a few-layer molybdenum disulfide nanosheet (intermediate product), thereby weakening the van der Waals force between the molybdenum disulfide layers and increasing the specific surface area, thereby improving the lubrication performance and dispersibility of molybdenum disulfide; further, the applicant introduces maleic anhydride to modify the above-mentioned few-layer molybdenum disulfide nanosheets, and the carboxyl groups in the maleic anhydride hydrolysis product form hydrogen bonds with the hydroxyl groups on the surface of molybdenum disulfide, and directionally coats the molybdenum disulfide particles, thereby improving the lipophilic and hydrophobic properties of molybdenum disulfide, thereby effectively improving the dispersibility of molybdenum disulfide in the polytetrafluoroethylene resin system.

[0034] Another aspect of the present invention further provides a method for preparing the thermoplastic wear-resistant composite material described in the above technical solution, comprising the following steps:

[0035] The thermoplastic wear-resistant composite material is obtained by mixing polytetrafluoroethylene, polyphenylene sulfide, modified aramid fiber and modified molybdenum disulfide, stirring, and compression molding at 350-380°C.

[0036] In another aspect, the present invention provides the application of the thermoplastic wear-resistant composite material described in the above technical solution, which is applied to pump bodies and bearing-related wear-resistant parts.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention uses polytetrafluoroethylene and polyphenylene sulfide as main components, adds modified aramid fiber and modified molybdenum disulfide to synthesize a thermoplastic wear-resistant composite material, and through the synergistic effect between the components, the thermoplastic wear-resistant composite material has the characteristics of low friction and high toughness.

[0039] (2) The present invention uses γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane as raw materials to prepare a hyperbranched polysiloxane to modify the amino-treated aramid fiber, and then introduces graphene oxide for modification, so that the surface activity and UV resistance of the aramid fiber are improved, thereby effectively improving the toughness of the thermoplastic wear-resistant composite material.

[0040] (3) The present invention uses an aqueous solution of N-methylpyrrolidone as a dispersant, adds sodium tartrate as an intercalation compound to exfoliate molybdenum disulfide to prepare a few-layer molybdenum disulfide nanosheets, and then introduces maleic anhydride for modification, so that the dispersibility of molybdenum disulfide is effectively improved, thereby making the thermoplastic wear-resistant composite material have good low friction properties.

[0041] (4) The composite material prepared by the present invention has the characteristics of good wear resistance, low friction and high toughness, and can be widely used in pump bodies, bearing-related wear-resistant parts, and has good commercial application value. DETAILED DESCRIPTION

[0042] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0043] In the following embodiments and comparative examples, except for modified aramid fiber and modified molybdenum disulfide, the other compound monomers and related reagents used can be purchased from the market. Among them, the polytetrafluoroethylene model is M111, purchased from Guangzhou Jingchen Plastic Co., Ltd.; the particle size of polyphenylene sulfide is 600 mesh, purchased from Shanghai Beisuyang International Trade Co., Ltd.; and the aramid fiber is purchased from Jiangxi Shuobang New Material Technology Co., Ltd.

[0044] Preparation Example 1

[0045] The synthesis method of modified aramid fiber A comprises the following steps:

[0046] (1) 24 g of γ-glycidyloxypropyl trimethoxysilane, 25 g of γ-methacryloxypropyl trimethoxysilane, 53 g of anhydrous ethanol and 24.5 g of deionized water were mixed, 37 wt % hydrochloric acid aqueous solution was added dropwise to adjust the pH to 5.5, heated to 60° C., stirred for 4 h, and vacuum dried at 60° C. for 4 h to obtain product 1 for later use;

[0047] (2) 20 ml of 98 wt% fuming nitric acid, 1 ml of 98 wt% concentrated sulfuric acid, 185 ml of acetic anhydride and 50 ml of glacial acetic acid were mixed and stirred for 30 min to obtain solution 1 for use; 6 g of potassium dihydrogen phosphate, 18 g of dipotassium hydrogen phosphate and 27.5 g of sodium borohydride were added to 200 ml of tetrahydrofuran and stirred for 30 min to obtain solution 2 for use; 15 g of aramid fiber was soaked in 100 ml of acetone, 100 ml of petroleum ether and 200 ml of deionized water in sequence for 5 min, heated to reflux at 40° C. for 4 h, filtered, vacuum dried at 80° C. for 12 h, then added to solution 1, stirred at 10° C. for 6 h, filtered, washed with deionized water, vacuum dried at 80° C. for 12 h, then added to solution 2, stirred for 24 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 12 h to obtain product 2 for use;

[0048] (3) Add 10 wt % sodium hydroxide aqueous solution to 20 g of the product 1 of step (1) to adjust the pH to 9, stir for 15 min, add 5 g of the product 2 of step (2), stir at 60 ° C for 4 h, filter, wash with anhydrous ethanol and deionized water three times in sequence, and vacuum dry at 80 ° C for 12 h to obtain product 3 for use;

[0049] (4) Add 2 g of dopamine hydrochloride to 300 ml of deionized water, stir for 20 min, add 0.5 mol / L sodium hydroxide aqueous solution to adjust the pH to 8, add 0.1 g of graphene oxide, stir at 30 ° C for 15 h, add 5 g of the product 3 of step (3), shake for 10 h, filter, wash with deionized water 3 times, and vacuum dry at 40 ° C for 12 h to obtain modified aramid fiber A.

[0050] Preparation Example 2

[0051] The specific implementation manner of the modified aramid fiber B is the same as that of the modified aramid fiber A, except that in step (1), the mass of γ-methacryloxypropyltrimethoxysilane is replaced with 23 g.

[0052] Preparation Example 3

[0053] The specific implementation manner of modified aramid fiber C is the same as that of modified aramid fiber A, except that in step (3), the mass of product 1 is replaced with 16.5 g.

[0054] Preparation Example 4

[0055] The specific implementation manner of modified aramid fiber D is the same as that of modified aramid fiber A, except that in step (4), the mass of graphene oxide is replaced with 0.03 g.

[0056] Preparation Example 5

[0057] The synthetic method of modified molybdenum disulfide A comprises the following steps:

[0058] 1) Add 5 g of molybdenum disulfide and 0.8 g of sodium tartrate to 100 ml of 80 wt% N-methylpyrrolidone aqueous solution, sonicate for 30 min, centrifuge, remove the supernatant, repeat the above operation 3 times, centrifuge, take the precipitate, wash 3 times with isopropanol, and vacuum dry at 60° C. for 24 h to obtain an intermediate product for use;

[0059] 2) Add 2 g of maleic anhydride to 50 ml of deionized water and stir for 30 min to obtain a solution for use. Add 5 g of the intermediate product of step 1) to 60 ml of anhydrous ethanol, ultrasonicate for 30 min, condense and reflux for 1 h, add the solution, stir for 2 h, filter, wash with anhydrous ethanol 3 times, vacuum dry at 60 ° C for 24 h, and crush to obtain modified molybdenum disulfide A.

[0060] Preparation Example 6

[0061] The specific implementation method of modified molybdenum disulfide B is the same as that of modified molybdenum disulfide A, except that in step 1), the mass of sodium tartrate is replaced with 0.3 g.

[0062] Preparation Example 7

[0063] The specific implementation manner of modified molybdenum disulfide C is the same as that of modified molybdenum disulfide A, except that in step 2), the mass of maleic anhydride is replaced with 1.2 g.

[0064] Example 1

[0065] A thermoplastic wear-resistant composite material comprises the following raw materials by weight: 70 parts of polytetrafluoroethylene, 30 parts of polyphenylene sulfide, 5 parts of modified aramid fiber A, and 3 parts of modified molybdenum disulfide A.

[0066] The preparation method of the thermoplastic wear-resistant composite material in this embodiment includes the following steps:

[0067] Polytetrafluoroethylene, polyphenylene sulfide, modified aramid fiber A and modified molybdenum disulfide A are mixed, stirred at 1000 rpm for 2 hours, and compression molded at 360° C. to obtain a thermoplastic wear-resistant composite material.

[0068] Example 2

[0069] A thermoplastic wear-resistant composite material comprises the following raw materials by weight: 65 parts of polytetrafluoroethylene, 25 parts of polyphenylene sulfide, 5 parts of modified aramid fiber A, and 1 part of modified molybdenum disulfide A.

[0070] The preparation method of the thermoplastic wear-resistant composite material in this embodiment includes the following steps:

[0071] Polytetrafluoroethylene, polyphenylene sulfide, modified aramid fiber A and modified molybdenum disulfide A are mixed, stirred at 1000 rpm for 2 hours, and compression molded at 350° C. to obtain a thermoplastic wear-resistant composite material.

[0072] Example 3

[0073] A thermoplastic wear-resistant composite material comprises the following raw materials by weight: 75 parts of polytetrafluoroethylene, 35 parts of polyphenylene sulfide, 5 parts of modified aramid fiber A, and 5 parts of modified molybdenum disulfide A.

[0074] The preparation method of the thermoplastic wear-resistant composite material in this embodiment includes the following steps:

[0075] Polytetrafluoroethylene, polyphenylene sulfide, modified aramid fiber A and modified molybdenum disulfide A are mixed, stirred at 1000 rpm for 2 hours, and compression molded at 380° C. to obtain a thermoplastic wear-resistant composite material.

[0076] Example 4

[0077] A thermoplastic wear-resistant composite material comprises the following raw materials by weight: 67 parts of polytetrafluoroethylene, 27 parts of polyphenylene sulfide, 3 parts of modified aramid fiber A, and 3 parts of modified molybdenum disulfide A.

[0078] The preparation method of the thermoplastic wear-resistant composite material in this embodiment is the same as that in Embodiment 1.

[0079] Example 5

[0080] A thermoplastic wear-resistant composite material comprises the following raw materials by weight: 72 parts of polytetrafluoroethylene, 32 parts of polyphenylene sulfide, 7 parts of modified aramid fiber A, and 3 parts of modified molybdenum disulfide A.

[0081] The preparation method of the thermoplastic wear-resistant composite material in this embodiment is the same as that in Embodiment 1.

[0082] Example 6

[0083] This embodiment provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the modified aramid fiber B replaces the modified aramid fiber A in equal amounts.

[0084] Example 7

[0085] This embodiment provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the modified aramid fiber C replaces the modified aramid fiber A in equal amounts.

[0086] Example 8

[0087] This embodiment provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the modified aramid fiber D replaces the modified aramid fiber A in equal amounts.

[0088] Example 9

[0089] This embodiment provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that modified molybdenum disulfide B replaces modified molybdenum disulfide A in equal amounts.

[0090] Example 10

[0091] This embodiment provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified molybdenum disulfide C replaces modified molybdenum disulfide A in equal amounts.

[0092] Comparative Example 1

[0093] This comparative example provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the modified aramid fiber A is replaced by aramid fiber.

[0094] Comparative Example 2

[0095] This comparative example provides a thermoplastic wear-resistant composite material and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the modified molybdenum disulfide A is replaced by molybdenum disulfide.

[0096] Performance Testing

[0097] The friction performance and toughness of the thermoplastic wear-resistant composite materials of Examples 1-10 and Comparative Examples 1-2 were tested. The test results are shown in Table 1.

[0098] (1) Friction performance

[0099] The friction coefficient of the thermoplastic wear-resistant composite material prepared in the embodiment and the comparative example was tested with reference to the standard GB / T 17754-2012.

[0100] (2) Toughness

[0101] The elongation at break of the thermoplastic wear-resistant composite materials prepared in the examples and comparative examples was tested with reference to standard GB / T 1040.2-2006, the test temperature was 23° C., and the speed was 20 mm / min.

[0102] Table 1

[0103] Group Friction coefficient Elongation at break (%) Example 1 0.09 210.8 Example 2 0.12 209.7 Example 3 0.11 210.3 Example 4 0.12 210.0 Example 5 0.11 210.2 Example 6 0.13 185.2 Example 7 0.14 185.0 Example 8 0.14 183.7 Example 9 0.16 205.4 Example 10 0.17 204.8 Comparative Example 1 0.16 174.6 Comparative Example 2 0.20 198.5

[0104] It can be seen from the data in Table 1 that the thermoplastic wear-resistant composite materials in Examples 1-5 of the present invention have the characteristics of low friction performance and high toughness as a whole. Among them, Examples 6-8 change the ratio between the key components in the synthesis process of modified aramid fiber, so that the surface activity and anti-ultraviolet performance of the modified aramid fiber are not well improved, and the toughness of the aramid fiber is affected, which leads to a significant decrease in the elongation at break of the composite material, that is, the toughness decreases, but has little effect on the friction performance; Examples 9-10 change the addition ratio of sodium tartrate and maleic anhydride in the modified molybdenum disulfide, so that the dispersibility of the modified molybdenum disulfide decreases, so that the modified molybdenum disulfide does not play a good lubricating role on the composite material, and then reflects the phenomenon of increased friction coefficient of the composite material, but has little effect on toughness; Comparative Examples 1-2 are to select aramid fiber and molybdenum disulfide to replace modified aramid fiber A and modified molybdenum disulfide A in equal amounts, respectively. Tests show that the toughness of Comparative Example 1 shows poor results and the friction performance of Comparative Example 2 shows poor results.

[0105] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermoplastic wear-resistant composite material, characterized in that: The thermoplastic wear-resistant composite material comprises the following raw materials in parts by weight: 65-75 parts of polytetrafluoroethylene, 25-35 parts of polyphenylene sulfide, 3-7 parts of modified aramid fiber, and 1-5 parts of modified molybdenum disulfide.

2. The thermoplastic wear-resistant composite material according to claim 1, characterized in that: The particle size of the polyphenylene sulfide is 550-650 meshes.

3. The thermoplastic wear-resistant composite material according to claim 1, characterized in that: The preparation method of the modified aramid fiber comprises the following steps: (1) γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, anhydrous ethanol and deionized water are mixed, the pH is adjusted to 5-6, the mixture is heated to 55-65° C., stirred for 3.5-4.5 h, and dried to obtain product 1 for later use; (2) Fuming nitric acid, concentrated sulfuric acid, acetic anhydride and glacial acetic acid are mixed and stirred to obtain solution 1 for use; potassium dihydrogen phosphate, dipotassium hydrogen phosphate and sodium borohydride are added to tetrahydrofuran and stirred to obtain solution 2 for use; aramid fiber is sequentially soaked in acetone, petroleum ether and deionized water, heated to reflux, filtered, vacuum dried and then added to solution 1, stirred at 5-15° C. for 5-7 h, filtered, washed, dried and then added to solution 2, stirred for 23-25 ​​h, filtered, washed and dried to obtain product 2 for use; (3) adding sodium hydroxide aqueous solution to the product 1 of step (1), stirring, adding the product 2 of step (2), stirring at 55-65° C. for 3.5-4.5 h, filtering, washing, and drying to obtain product 3 for standby use; (4) Add dopamine hydrochloride to deionized water, stir, add sodium hydroxide aqueous solution, add graphene oxide, stir at 20-40° C. for 14-16 h, add the product 3 of step (3), shake for 9-11 h, filter, wash, and dry to obtain modified aramid fiber.

4. The thermoplastic wear-resistant composite material according to claim 3, characterized in that: In the step (3), the mass ratio of product 2 to product 1 is 1:(3.5-4.5).

5. The thermoplastic wear-resistant composite material according to claim 3, characterized in that: In the step (4), the mass ratio of the product 3 to graphene oxide is 1:(0.01-0.03).

6. The thermoplastic wear-resistant composite material according to claim 1, characterized in that: The preparation method of the modified molybdenum disulfide comprises the following steps: 1) adding molybdenum disulfide and sodium tartrate to an aqueous solution of N-methylpyrrolidone, ultrasonicating, centrifuging, removing the supernatant, repeating the above operation, centrifuging, taking the precipitate, washing, drying, and obtaining an intermediate product for standby use; 2) adding maleic anhydride into deionized water, stirring to obtain a solution for use, adding the intermediate product of step 1) into anhydrous ethanol, ultrasonicating, condensing and refluxing, adding the solution, stirring, filtering, washing, drying, and crushing to obtain modified molybdenum disulfide.

7. The thermoplastic wear-resistant composite material according to claim 6, characterized in that: In the step 1), the mass ratio of molybdenum disulfide to sodium tartrate is 1:(0.1-0.2).

8. The thermoplastic wear-resistant composite material according to claim 6, characterized in that: In the step 2), the mass ratio of the intermediate product to maleic anhydride is 1:(0.3-0.5).

9. A method for preparing the thermoplastic wear-resistant composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The thermoplastic wear-resistant composite material is obtained by mixing polytetrafluoroethylene, polyphenylene sulfide, modified aramid fiber and modified molybdenum disulfide, stirring, and compression molding at 350-380°C.

10. An application of the thermoplastic wear-resistant composite material according to any one of claims 1 to 8, characterized in that: Applied to pump bodies, bearing-related wear-resistant parts.

Citation Information

Patent Citations

  • Assorted and reinforced high-performance composites for bearing and their preparation method and use

    CN1699474A

  • Surface modified aramid fiber and preparation method thereof

    CN105603717A

  • High-toughness tear-resistance polyethylene cable material

    CN106750799A

  • Reinforcing and toughening high temperature-resistant material used for road and production method thereof

    CN108440958A

  • New energy battery shell drawing oil and preparation method thereof

    CN115595197A

Cited By

  • High-barrier flexible heating carbon crystal protective film

    CN120944464A

  • High-barrier flexible heating carbon crystal protective film

    CN120944464B